Tafsir Al-Qu’ran di Madura: Periodisasi, Metodologi, dan Ideologi - Ulfatun Hasanah (Institut Ilmu Keislaman Annuqayah, 2019)
The studies of local interpretation are considerably limited, specifically regarding Madurese interpretation of al-Quran. Most of the researchers tend to not be concerned since the studies are deemed similar to other common interpretations in Nusantara. In fact, the diversity in interpretation is not only influenced by the perspective in interpreting word by word but also by the location of the interpreter itself. The socio-cultural dimension encompassing interpretation becomes one of the decisive points to apprehend the methodology and ideology. Therefore, local culture is substantially significant in affirming the real situation of the development of the study of interpretation in general, especially with respect to the large scope of the influences of Islam Nusantara’s network. In light of that, local interpretation should be explored completely to expose the existence of Madurese interpretation. The periodization is divided into three phases, namely birth, growth, and development period. In each period, the methodologies used in the interpretations, such as the forms, styles, and methods, are analyzed carefully. The ideology, on the other hand, is founded on Ahlussunnah wal jamaah.